Associations between repeated ultrasound measures of fetal growth and biomarkers of maternal oxidative stress and inflammation in pregnancy. (8th July 2018) - Ferguson, Kelly K.; Kamai, Elizabeth M.; Cantonwine, David E.; Mukherjee, Bhramar; Meeker, John D.; McElrath, Thomas F.
Abstract : Problem: Perturbations in normal fetal growth during pregnancy are associated with poor child and adult health outcomes. Inflammation and oxidative stress are recognized as important mechanisms in preeclampsia and preterm birth but have been examined less in relation to fetal growth. We hypothesized that maternal inflammation and oxidative stress in pregnancy would be associated with reduced fetal growth and sought to identify windows of vulnerability. Method of study: In a secondary analysis of 482 women from the LIFECODES birth cohort study, we measured inflammation (C‐reactive protein [CRP] and the cytokines IL‐1β, IL‐6, IL‐10, and TNF‐α) and oxidative stress (8‐isoprostane and 8‐hydroxydeoxyguanosine [8‐OHdG]) biomarkers in plasma and urine, respectively, at four time points during pregnancy. We examined associations between repeated measures of each marker and ultrasound (head and abdominal circumference, femur length, and a summary measure of estimated fetal weight) as well as delivery (birthweight) metrics of growth. Results: In adjusted repeated‐measures models, an interquartile range (IQR) increase in CRP was associated with a 0.12 standard deviation decrease in fetal weight z ‐score (95% confidence interval, CI, −0.21, −0.02), which corresponds to approximately 50 g at 40‐week gestation. The association was greatest in magnitude (ie, most negative) with CRP measured later in pregnancy. Oxidative stress markers were not associated with fetal weight, although both were inversely associated with head circumference and femur length. Conclusion: Inflammation and oxidative stress markers measured later in pregnancy were associated with reduced fetal growth as measured by repeated ultrasound scans.